JURISDICTIONAL IMPLICATIONS OF LAW NO. 16 YEAR 2019 CONCERNING MARRIAGE ON MARRIAGE CONDITIONS - Dyah Retno Pitasari; Gloria M. P Djurubassa (Fakultas Hukum Universitas Djuanda Bogor, 2022)
This research is the normative juridical research with the approach of the legislation. The problems are how yuridical implication decisions the constitutional court against the requirements a marriage in law No. 1 year 1974 to license and how legal awareness in marriage in North Halmahera. The materially requirement about the ideal age it’s not enough to be understood by youth in North Halmahera, because there are still many early marriage. The formil requirements of marriage also are still highly scanty. The marriage only held in the church, and in fact the administration orderliness in civil registration has not been applied. Divorce rate is still experiencing an increase in North Halmahera. Apart from not yet adequate legal awareness of youth related the ideal age of marriage, the divorce also because of the recent escalation of corona virus that causes the economy of a family and cause divorce.